Gender differences in the stickhandling technique of young field hockey players - Yurievich, Shishkov Igor (Journal of Current Health Sciences, 2023)
The article presents preliminary results of research of technical fitness of young field hockey players (boys and girls) of 9-16 years old using the test "Dribbling on the spot in 15 sec.", which evaluates the number of left hand turns as an indicator of hockey player's technical fitness. And also a comparative analysis of the strength of the left and right hands of young hockey players depending on age was given. It is revealed that from the age of 14 the girls have the dominance of the left hand strength over the right hand, as the left hand in field hockey has the leading value.